Epi-Olmecs and Epi-Romans: The Unified Theory of Politics, History, and the Power of Analogies - Christopher Binetti (Polit Journal Scientific Journal of Politics, 2024)
Scholars are not using the proper analytical tools for comparing polities and cultures even within the same Civilization. The Unified Theory of Politics is a new approach to History and Politics that allows for comparison across the four Civilizations of the world (Western, Central, Eastern, and Mesoamerican). Mesoamerica is a Civilization made up of numerous civilizations. These civilizations are not compared to each other properly, with Mayans, Olmecs, and Epi-Olmecs all considered as equal units of analysis, which is not true. At the same time, within the Western Civilization, ancient Italy is not being properly analyzed either. The Latins, Romans, and Oscans are equal units of analysis either, yet the categorization of cultures and polities here is little better than in ancient Mesoamerica. The Unified Theory of Politics allows us to bridge seemingly impossible differences in culture, time, and place. This gives us the analytical and comparative tools to analogize between Civilizations. This article will show how the Unified Theory of Politics works by demonstrating not only that the Mayans and the Oscans are comparable with each other, but also that Olmecs and Romans are comparable with one another. This leads to the analogy of: “The Mayans are to the Oscans as the Olmecs are to the Romans”. Also, the article will demonstrably prove that Italians are Epi-Romans. This article will thus show that the Unified Theory of Politics allows us to compare any polity or culture with writing to any other polity or culture with writing, regardless of culture, place, or time.